Cost-effectiveness analysis of penpulimab combined with paclitaxel and carboplatin as a first-line treatment for metastatic squamous non-small cell lung cancer in China - Yuan Gao; Liangxiao Wang; Na Lv; Chunyan Yan; Xuechen Huo; Ruigang Diao (BMJ Open)
Objectives Penpulimab is a novel programmed death-1 (PD-1) inhibitor that has been approved in China for use in combination with chemotherapy as a first-line treatment for locally advanced or metastatic squamous non-small cell lung cancer (sq-NSCLC). However, the cost-effectiveness of this treatment in China remains to be determined. In this study, we aimed to assess the cost-effectiveness of penpulimab combined with paclitaxel and carboplatin for metastatic sq-NSCLC.Design Based on the AK105-302 trial (NCT03866993), a Markov model was created to evaluate the disease progression of metastatic sq-NSCLC patients over 10 years. The model included progression-free survival, progressive disease and death. The utility values were derived from published literature. Sensitivity studies were used to assess the robustness of the model outputs.Setting The Chinese healthcare system perspective.Participants A hypothetical Chinese cohort of patients with locally advanced or metastatic sq-NSCLC.Interventions Penpulimab plus chemotherapy versus chemotherapy.Primary outcome measure Costs, quality-adjusted life years (QALYs) and incremental cost-effectiveness ratio (ICER).Results Compared with the chemotherapy alone group, the cost of penpulimab plus chemotherapy increased by US$3717.72, with an increase of 0.43 QALYs. The ICER was US$8625.78/QALY, which was well below the willingness-to-pay threshold of US$38 052/QALY. This demonstrated higher cost-effectiveness benefits, as confirmed by the sensitivity analysis results.Conclusions Under the Chinese health system, penpulimab plus paclitaxel and carboplatin is cost-effective for metastatic sq-NSCLC patients and can be used as an economical and effective treatment option.